A Family with a High Incidence of Migraine and Vestibular Migraine and a Case of Menière’s Disease - Marco Familiari; Omar Gatti; Iacopo Cangiano; Roberto Teggi (Case Reports in Medicine)
Vestibular migraine (VM) and Menière’s disease (MD) are common neurotological disorders causing episodic vertigo. Sometimes, VM is accompanied by cochlear symptoms suggestive for MD. Therefore, in those cases, the differential diagnosis between the two disorders can be difficult. Moreover, a comorbidity with migraine in MD patients is widely reported, up to the hypothesis of a possible MD-VM overlapping syndrome. In this brief case report, we consider the clinical history of a family presenting high incidence of subjects fulfilling the diagnostic criteria of VM and single case fulfilling criteria for definite MD. The relationship between VM and MD is still under debate; anyway, it can be speculated that commonly shared genetic mutations could play a role as predisposing factors in both disorders. A congenital nystagmus in the family was present too, but its correlation with the other conditions is still not clear. Future goal of our work will be to assess genetics in this family.